Discovery of two novel Flavobacterium species with potential for complex polysaccharide degradation - Xu-Dong Lian; Yong Guan; Yue Jiang; Dong-Heui Kwak; Mi-Kyung Lee; Zhun Li (Scientific Reports)
Abstract Polysaccharides are recognized for their extensive biological functions, holding significant promise for applications in both medicine and food industries. However, their utilization is frequently constrained by challenges such as high molecular weights and indistinct sugar chain structures. Recently, two novel bacterial strains, N6T and J3T, were isolated from the Nakdong River in Korea. These strains, which belong to the phylum Bacteroidota, are Gram-stain-negative, non-motile, aerobic, rod-shaped bacteria and have shown polysaccharide-degrading capabilities. Through comprehensive analyses, including 16S rRNA gene sequencing, whole-genome sequencing, and detailed morphological, physiological, and chemotaxonomic characterizations, these strains have been identified as new species within the genus Flavobacterium. KEGG pathway analysis further confirmed their robust capabilities for carbohydrate utilization. Additional investigations using the dbCAN and dbCAN-PUL databases identified the presence of carbohydrate-hydrolyzing enzymes (CAZymes) and polysaccharide utilization loci (PULs) within these strains, suggesting their potential to degrade various polysaccharides. Subsequent in vitro growth experiments demonstrated that strains N6T and J3T can degrade chitin, β-glucan, κ-carrageenan, and cellulose. Given their diverse polysaccharide degradation abilities, these strains are formally proposed to be named Flavobacterium polysaccharolyticum sp. nov. and Flavobacterium aureirubrum sp. nov. The type strains are designated as N6T (= KCTC 102173T = GDMCC 1.4609T) and J3T (= KCTC 102172T = GDMCC 1.4608T), respectively.